The Noise Indoors: Improvisation, Community, and #StayHome - Dias, José; Hunter, Anton (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
This article is a reflection of a collaboration between musicians Anton Hunter and José Dias who, in April 2020, organised a free, biweekly improvisation streaming festival, which ran for three weeks, entitled The Noise Indoors (TNI). Devised as a way of encouraging musicians and fans to stay home by providing the chance to continue experiencing and celebrating improvised music during confinement, TNI gathered twenty-eight artists based in seventeen cities across Europe who filmed solo or duet performances in their homes. As TNI progressed, this festival became a platform for sharing each artist’s intimate music-making, as well as an opportunity for networking and community building. Using an eclectic mix of critical and dialogic writing styles (including field notes and text messages), they reflect on their experiences as researchers, musicians, and curators who organised and participated in TNI, and consider its wider implications.